Efeito da crisina sobre as alterações comportamentais e neuroquímicos em um modelo da doença de parkinson causada pela 6-hidroxidopamina em camundongos - Goes, André Tiago Rossito (2018)
Parkinson's disease (PD) is characterized by a progressive degeneration of dopaminergic neurons of the nigrostriatal system and dopamine depletion (DA) in the striatum. Chrysin has been shown to be a promising non-pharmacological approach to reducing the risk of neurodegenerative diseases. This study investigated the potential neuroprotective effect of chrysin in an animal model of PD induced by 6-hydroxydopamine (6-OHDA) in mice. The present study demonstrated that a dose of chrysin (10 mg / kg / day po) for 28 days was effective in modulating the following changes resulting from exposure to 6-OHDA: attenuating the change in type-depressive behavior (tail suspension test) (GPx, GSH, GST, GH), reduce levels of proinflammatory cytokines (TNF-α, IFN-γ, IL-1β) , IL-2 and IL-6), as well as attenuated the reduction of AD, DOPAC and HVA levels. In addition, it prevented the reduction of TH + neurons caused by exposure to 6-OHDA, in addition to raising the BDNF, GDNF and NGF levels in the striatum of mice. These results reinforce that one of the neuroproteror effects induced by chrysin in PD is due to the antioxidant, anti-inflammatory and modulating effects of neurotrophins. Therefore, the present study suggests that chrysin attenuates the 6-OHDA-induced cognitive and motor declines, depression, oxidative stress and neuroinflammation by supporting the hypothesis that chrysin may be used as a adjuvant treatment to the current pharmacological treatment to reduce the signs of PD